Finite element analysis of centrifugal impellers - Sham Sunder, K. (Cranfield University, 1981)
A three-dimensional method of stress analysis using finite element techniques is presented for determining the stress distribution in centrifugal impellers. It can treat all of the three types of loading possible in an inpeller, viz centrifugal, thermal and fluid. The method has no known limitations with regards to the geometric factors such as asymnetry of disk, blade curvature, presence of a cover disk or shroud, single or double sided impeller etc. A comparison of results with available experimental photoelastic results is presented with good agreement. The problem of the inter-blade bending effect, on the stress characteristics of an impeller, with relevance to the number of blades is studied in some depth. An insight into the effect of blade curvature on the stress characteristics of an impeller is also achieved. As an extension of the above work, a method is proposed for the analysis of the dynamic, behaviour of impe1lers, achieving a reasonable degree of success, particularly considering the limited period of time that was available for such an exercise.